Macro and micronutrients assessment in caregivers of elderly people: a food consumption issue (Research, Society and Development, 2022)
This study aims to investigate the food consumption of caregivers of elderly people before and after the food workshops. In this sense, a cross-sectional study with 31 participants, whose evaluated population consisted of caregivers from the Health Care Center for the Elderly and their Caregivers (CASIC) of the Fluminense Federal University (UFF), they were submitted to the ELSA questionnaire. A total of N=14 (45.2%) formal caregivers and N=17 (54.8%) informal caregivers were found. In relation to food consumption, a significant reduction in total sugar consumption was found (p-value